Psychological and Propaganda Operations as a Form of Hybrid War - Proroković, Dušan; Parezanović, Marko (NBP. Nauka, bezbednosti, policija, 2024)
Psychological and propaganda operations are inseparable part of hybrid warfare. The rapid complication of overall relations in the international community, especially since the beginning of 2022, has led to tectonic upheavals in the world order, which have caused numerous changes in front of our eyes. The world is changing today, perhaps faster than ever. In such complex political and security, economic and social circumstances, models of hybrid warfare gained additional importance and in a certain way, conditionally speaking, became an inseparable part of the foreign policy of the leading powers. In addition, hybrid actions of a psychological and propaganda nature have become an inseparable part of international relations. This paper first analyzes the conceptual definition of the terms hybrid war, psychological and propaganda operations, and then explains the cause-and-effect relationships and examines their consequences on the offensive and defensive actors of international relations. Among the conclusions is the assertion that defensive actors may be completely unaware that a hybrid war is actually being waged against them by undertaking psychological and propaganda operations.
Keywords: psychological operations; propaganda operations; hybrid war; conventional war